The influence of economic cyclicality on the formation of economic security of construction enterprises - Palagitsky, Viktor; Skrypnyk, Andriy; Skrypnyk, Olga (Ways to Improve Construction Efficiency, 2025)
The article examines the economic security of construction enterprises in the context of economic cyclicality. Although economic security has been widely studied in economic theory, its adaptation to the specific characteristics of the construction sector and to modern macroeconomic and geopolitical challenges remains insufficiently systematized. The purpose of the study is to identify key exogenous and endogenous factors that influence a construction enterprise and determine their role in ensuring its economic security at different phases of the economic cycle Kitchin. The study is based on the integration of systemic and process approaches. Within the systemic framework, economic security is considered as a dynamic, hierarchically structured system of interconnected subsystems (financial, production, personnel, innovation, etc.), the balanced interaction of which ensures the stability of the enterprise. The process approach emphasizes managerial and organizational measures aimed at protecting the interests of the enterprise from internal and external threats at different phases of the economic cycle Kitchin. The combination of these approaches provides a comprehensive methodological framework for analyzing security in cyclical conditions. The construction industry is characterized as a highly pro-cyclical sector, sensitive to fluctuations in investment demand, interest rates, inflation, exchange rate volatility, and government regulatory policies. Its long investment cycle and high capital intensity increase vulnerability to macroeconomic shocks. During economic growth, expanded access to credit and increased demand stimulate development; during recessions, reduced investment, liquidity shortages, and payment delays weaken financial stability. War-related and geopolitical factors further increase risks and uncertainty. The article substantiates the classification of economic security factors into exogenous (macroeconomic, institutional, industry, geopolitical) and endogenous (internal resources and management decisions). Particular attention is paid to financial and economic, production and technological, project and management, personnel and innovation and organizational factors as key determinants of the economic security of a construction enterprise. The matrix linking endogenous factors with the phases of the economic cycle demonstrates the nonlinear and asymmetric impact of cyclicality. Financial flexibility is critically important during recessions; production capacity is crucial during expansion; innovative adaptability becomes important during transitional phases. The study concludes that effective countercyclical management, the formation of reserves during growth and the use of accumulated potential during recessions, are fundamental for ensuring a high level of economic security of construction enterprises.